Fatores de risco e conhecimento de idosos sobre doença renal crônica - Millena Freire Delgado; Isabel Neves Duarte Lisboa; Maria Isabel da Conceição Dias Fernandes; Ana Carolina Costa Carino; Renata Marinho Fernandes; Ana Luisa Brandão de Carvalho Lira (Universidade Federal do Ceará, 2017)
Objective: to analyze the relationship between the risk factors and the elderly people knowledge about chronic kidney disease. Methods: this study is a cross-sectional research with 100 elderly enrolled in basic units, using a semi-structured interview. Data were analyzed using descriptive and inferential statistics. Results: most elderly people had adequate knowledge about the disease and prevention, but poor knowledge about hemodialysis. Regarding the risk factors in the elderly investigated, increased are highlighted and statistical significance of waist circumference (p=0.049), smoking (p=0.022) and alcohol consumption (p=0.013). Conclusion: relationships between risk factors as smoking, alcoholism, increased abdominal circumference, and the knowledge of the elderly about chronic kidney disease were identified.